The Improvement of Working Posture and Ergonomic Workplace Stretching Decreased Musculoskeletal Complaint and Fatigue and Increased Productivity of Nurses - Suwartini, Ni Luh Gede; Tirtayasa, Ketut; Handari Adiputra, Luh Made Indah Sri (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2020)
General fatigue complaints and musculoskeletal disorders are two of the most common symptoms experienced by dialysis nurses, as the products of the poor ergonomic working poses. Ergonomic intervention and stretching in the workplace are needed to reduce the symptoms. Unnatural pose has a potential to develop general fatigue and musculoskeletal disorders in hemodialysis room where each nurse in every shift is in charge to take care of four patients. The study aims to investigate the improvement of poses of work ergonomically by using ergonomic workplace stretching to reduce complaints in musculoskeletal and general fatigue which in turn can expectedly improve work productivity in hemodialysis room. This study is an experimental study with treatment by subject design. The study was conducted in hemodialysis unit in Wangaya Regional Public Hospital (WRPH) Denpasar from October until December 2019 with 11 people as the participants. As the result, there is no significant difference in the average of musculoskeletal complaints before working with p=0.350 (p>0.05). Meanwhile, the average of musculoskeletal complaints of nurse after working shows a significant difference that is p=0.001 (p<0.05). The analysis result indicates that there is a significant decrease in musculoskeletal complaints, which is 36.18%. The average of general fatigue before working shows no significant difference in score, that is p=0.350 (p>0.05). In the other side, there is a significant difference in score after working with p=0.001 (p<0.05). The analysis result reveals that there is a significant decrease in general fatigue for 66.97%. A significant improvement is shown in the productivity average with p=0.001 (p<0.05). The conclusion of this study is the improvement in poses of work and ergonomic workplace stretching have reduced the complaints in musculoskeletal and general fatigue and also improve nurses’ working productivity in hemodialysis unit.